Sosialisasi Pembuatan Pokak Jahe Untuk Meningkatkan Imunitas Dimasa Pandemi Covid-19 di Sumberkedawung Leces Probolinggo - Widayanto, Mutinda Teguh (LPPPM STAI Darul Hikmah Bangkalan, 2021)
The Covid-19 pandemic that has hit almost all regions of the world has affected various sectors of people's lives. Restrictions on community activities due to avoiding the spread of the virus prevent activities from being carried out properly. The educational, social and economic sectors coud not be avoided by this pandemic. Efforts to deal with virus transmission were also made. Various studies have been conducted to overcome these problems. One of the factors that can overcome the impact of a virus attack is the presence of good body immunity. The traditional Pokak Jahe drink is known to contain herbal ingredients that have properties that can increase the body's immunity from virus attacks. This community service activity in the form of socializing the making of Pokak Jahe aims to provide an understanding of the benefits and to socialize how to make Pokak Jahe drink as a traditional drink that is useful for increasing body immunity during the Covid-19 pandemic. It is hoped that the community will understand these benefits and be able to make Pokak Jake drinks for consumption and commercialization so that they can increase their immunity